Conversion of Glucose to 5-Hydroxymethylfurfural in a Microreactor - Tongtummachat, Tiprawee; Akkarawatkhoosith, Nattee; Kaewchada, Amaraporn; Jaree, Attasak (Frontiers in Chemistry, 2020)
5‑hydroxymethylfurfural (5-HMF) is one of the key bio-based platform chemicals for the production of high-value chemicals and fuels. The conventional production of 5-HMF from biomass is confronted by the relatively low yield and high production cost. In this work, the enhancement of a continuous catalytic synthesis of 5-HMF in a biphasic-dispersed flow reactor was proposed. Glucose, hydrochloric acid, and methyl isobutyl ketone (MIBK) were used as a low-cost raw material, catalyst, and organic solvent, respectively. The main factors (reaction temperature, residence time, solvent amount, and catalyst concentration) affecting the yield and selectivity of 5-HMF were studied. The 5-HMF yield of 81.7% and 5-HMF selectivity of 89.8% were achieved at the residence time of 3 min, reaction temperature of 180 C, the volumetric flow rate of aqueous phase to organic phase of 0.5:1, and catalyst concentration of 0.15 M. The yield and selectivity of 5-HMF obtained from the biphasic system were significantly higher than that obtained from the single phase system. The superior 5-HMF production in our system in terms of operating conditions was presented when compared to the literature data. Furthermore, the continuous process for removing HCl from the aqueous product was also proposed.